Accumulation of T-cell-suppressive PD-L1 high extracellular vesicles is associated with GvHD and might impact GvL efficacy - Baur, Rebecca; Karl, Franziska; Böttcher-Loschinski, Romy; Stoll, Andrej; Völkl, Simon; Gießl, Andreas; Flamann, Cindy; Bruns, Heiko; Schlötzer-Schrehardt, Ursula; Böttcher, Martin; Schewe, Denis M.; Fischer, Thomas; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) represents the only curative treatment option for a number of hemato-oncological disorders. In fact, allo-HSCT is considered as one of the most successful immunotherapies as its clinical efficacy is based on the donor T-cells' capacity to control residual disease. This process is known as the graft-versus-leukemia (GvL) reaction. However, alloreactive T-cells can also recognize the host as foreign and trigger a systemic potentially life-threatening inflammatory disorder termed graft-versus-host disease (GvHD). A better understanding of the underlying mechanisms that lead to GvHD or disease relapse could help us to improve efficacy and safety of allo-HSCT. In recent years, extracellular vesicles (EVs) have emerged as critical components of intercellular crosstalk. Cancer-associated EVs that express the immune checkpoint molecule programmed death-ligand 1 (PD-L1) can suppress T-cell responses and thus contribute to immune escape. At the same time, it has been observed that inflammation triggers PD-L1 expression as part of a negative feedback network. Here, we investigated whether circulating EVs following allo-HSCT express PD-L1 and tested their efficacy to suppress the ability of (autologous) T-cells to effectively target AML blasts. Finally, we assessed the link between PD-L1 levels on EVs to (T-)cell reconstitution, GvHD, and disease relapse. We were able to detect PD-L1 + EVs that reached a peak PD-L1 expression at 6 weeks post allo-HSCT. Development of acute GvHD was linked to the emergence of PD-L1 high EVs following allo-HSCT. Moreover, PD-L1 levels correlated positively with GvHD grade and declined (only) on successful therapeutic intervention. T-cell-inhibitory capacity was higher in PD-L1 high EVs as compared with their PD-L1 low counterparts and could be antagonized using PD-L1/PD-1 blocking antibodies. Abundance of T-cell-suppressive PD-L1 high EVs appears to also impact GvL efficacy as patients were at higher risk for relapse. Finally, patients of PD-L1 high cohort displayed a reduced overall survival.Taken together, we show that PD-L1-expressing EVs are present following allo-HSCT. PD-L1 levels on EVs correlate with their ability to suppress T-cells and the occurrence of GvHD. The latter observation may indicate a negative feedback mechanism to control inflammatory (GvHD) activity. This intrinsic immunosuppression could subsequently promote disease relapse.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Immune Evation; T-Lymphocytes; Transplantation Immunology

Acod1-mediated inhibition of aerobic glycolysis suppresses osteoclast differentiation and attenuates bone erosion in arthritis - Kachler, Katerina; Andreev, Darja; Thapa, Shreeya; Royzman, Dmytro; Gießl, Andreas; Karuppusamy, Shobika; Llerins Perez, Mireia; Liu, Mengdan; Hofmann, Jörg; Geßner, Arne; Meng, Xianyi; Rauber, Simon; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: Metabolic changes are crucially involved in osteoclast development and may contribute to bone degradation in rheumatoid arthritis (RA). The enzyme aconitate decarboxylase 1 (Acod1) is known to link the cellular function of monocyte-derived macrophages to their metabolic status. As osteoclasts derive from the monocyte lineage, we hypothesised a role for Acod1 and its metabolite itaconate in osteoclast differentiation and arthritis-associated bone loss. Methods: Itaconate levels were measured in human peripheral blood mononuclear cells (PBMCs) of patients with RA and healthy controls by mass spectrometry. Human and murine osteoclasts were treated with the itaconate derivative 4-octyl-itaconate (4-OI) in vitro. We examined the impact of Acod1-deficiency and 4-OI treatment on bone erosion in mice using K/BxN serum-induced arthritis and human TNF transgenic (hTNFtg) mice. SCENITH and extracellular flux analyses were used to evaluate the metabolic activity of osteoclasts and osteoclast progenitors. Acod1-dependent and itaconate-dependent changes in the osteoclast transcriptome were identified by RNA sequencing. CRISPR/Cas9 gene editing was used to investigate the role of hypoxia-inducible factor (Hif)-1α in Acod1-mediated regulation of osteoclast development. Results: Itaconate levels in PBMCs from patients with RA were inversely correlated with disease activity. Acod1-deficient mice exhibited increased osteoclast numbers and bone erosion in experimental arthritis while 4-OI treatment alleviated inflammatory bone loss in vivo and inhibited human and murine osteoclast differentiation in vitro. Mechanistically, Acod1 suppressed osteoclast differentiation by inhibiting succinate dehydrogenase-dependent production of reactive oxygen species and Hif1α-mediated induction of aerobic glycolysis. Conclusion: Acod1 and itaconate are crucial regulators of osteoclast differentiation and bone loss in inflammatory arthritis.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Bone Density; Inflammation; Osteoporosis

An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A.; Szymanska, Katarzyna; Nguyen, Thanh-Minh T.; Racher, Hilary; Phelps, Ian G.; Toedts, Grischa; Kennedy, Julie; Wunderlich, Kirsten A.; Sorusch, Nasrin; Abdelhamed, Zakia A.; et al. (Nature Cell Biology, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
EVALuna2:9277

Association of Rare CYP39A1 Variants with Exfoliation Syndrome Involving the Anterior Chamber of the Eye - Li, Zheng; Wang, Zhenxun; Lee, Mei Chin; Zenkel, Matthias; Peh, Esther; Ozaki, Mineo; Topouzis, Fotis; Nakano, Satoko; Chan, Anita; Chen, Shuwen; Williams, Susan E.I.; Orr, Andrew; et al. (Journal of the American Medical Association, 2021)
Importance: Exfoliation syndrome is a systemic disorder characterized by progressive accumulation of abnormal fibrillar protein aggregates manifesting clinically in the anterior chamber of the eye. This disorder is the most commonly known cause of glaucoma and a major cause of irreversible blindness. Objective: To determine if exfoliation syndrome is associated with rare, protein-changing variants predicted to impair protein function. Design, Setting, and Participants: A 2-stage, case-control, whole-exome sequencing association study with a discovery cohort and 2 independently ascertained validation cohorts. Study participants from 14 countries were enrolled between February 1999 and December 2019. The date of last clinical follow-up was December 2019. Affected individuals had exfoliation material on anterior segment structures of at least 1 eye as visualized by slit lamp examination. Unaffected individuals had no signs of exfoliation syndrome. Exposures: Rare, coding-sequence genetic variants predicted to be damaging by bioinformatic algorithms trained to recognize alterations that impair protein function. Main Outcomes and Measures: The primary outcome was the presence of exfoliation syndrome. Exome-wide significance for detected variants was defined as P < 2.5 × 10-6. The secondary outcomes included biochemical enzymatic assays and gene expression analyses. Results: The discovery cohort included 4028 participants with exfoliation syndrome (median age, 78 years [interquartile range, 73-83 years]; 2377 [59.0%] women) and 5638 participants without exfoliation syndrome (median age, 72 years [interquartile range, 65-78 years]; 3159 [56.0%] women). In the discovery cohort, persons with exfoliation syndrome, compared with those without exfoliation syndrome, were significantly more likely to carry damaging CYP39A1 variants (1.3% vs 0.30%, respectively; odds ratio, 3.55 [95% CI, 2.07-6.10]; P = 6.1 × 10-7). This outcome was validated in 2 independent cohorts. The first validation cohort included 2337 individuals with exfoliation syndrome (median age, 74 years; 1132 women; n = 1934 with demographic data) and 2813 individuals without exfoliation syndrome (median age, 72 years; 1287 women; n = 2421 with demographic data). The second validation cohort included 1663 individuals with exfoliation syndrome (median age, 75 years; 587 women; n = 1064 with demographic data) and 3962 individuals without exfoliation syndrome (median age, 74 years; 951 women; n = 1555 with demographic data). Of the individuals from both validation cohorts, 5.2% with exfoliation syndrome carried CYP39A1 damaging alleles vs 3.1% without exfoliation syndrome (odds ratio, 1.82 [95% CI, 1.47-2.26]; P <.001). Biochemical assays classified 34 of 42 damaging CYP39A1 alleles as functionally deficient (median reduction in enzymatic activity compared with wild-type CYP39A1, 94.4% [interquartile range, 78.7%-98.2%] for the 34 deficient variants). CYP39A1 transcript expression was 47% lower (95% CI, 30%-64% lower; P <.001) in ciliary body tissues from individuals with exfoliation syndrome compared with individuals without exfoliation syndrome. Conclusions and Relevance: In this whole-exome sequencing case-control study, presence of exfoliation syndrome was significantly associated with carriage of functionally deficient CYP39A1 sequence variants. Further research is needed to understand the clinical implications of these findings.
CRIS-Team Scopus Importer:2021-03-05

Autophagy regulates TNFα-mediated joint destruction in experimental arthritis - Lin, Neng-Yu; Beyer, Christian; Gießl, Andreas; Kireva, Trayana; Scholtysek, Carina; Uderhardt, Stefan; Munoz, Luis Enrique; Dees, Clara; Distler, Alfiya; Wirtz, Stefan; Krönke, Gerhard; Spencer, Brian; et al. (Annals of the Rheumatic Diseases, 2013)
Objectives: Autophagy is a homeostatic process to recycle dispensable and damaged cell organelles. Dysregulation of autophagic pathways has recently been implicated in the pathogenesis of various diseases. Here, we investigated the role of autophagy during joint destruction in arthritis. Methods: Autophagy in osteoclasts was analysed in vitro and ex vivo by transmission electron microscopy, Western blotting and immunohistochemistry for Beclin1 and Atg7. Small molecule inhibitors, LysMCre-mediated knockout of Atg7 and lentiviral overexpression of Beclin1 were used to modulate autophagy in vitro and in vivo. Osteoclast differentiation markers were quantified by realtime PCR. The extent of bone and cartilage destruction was analysed in human tumour necrosis factor α transgenic (hTNFα tg) mice after adoptive transfer with myeloid specific Atg7-deficient bone marrow. Results: Autophagy was activated in osteoclasts of human rheumatoid arthritis (RA) showing increased expression of Beclin1 and Atg7. TNFα potently induced the expression of autophagy-related genes and activated autophagy in vitro and in vivo. Activation of autophagy by overexpression of Beclin1-induced osteoclastogenesis and enhanced the resorptive capacity of cultured osteoclasts, whereas pharmacologic or genetic inactivation of autophagy prevented osteoclast differentiation. Arthritic hTNFα tg mice transplanted with Atg7fl/fl×LysMCre+ bone marrow cells (BMC) showed reduced numbers of osteoclasts and were protected from TNFα-induced bone erosion, proteoglycan loss and chondrocyte death. Conclusions: These findings demonstrate that autophagy is activated in RA in a TNFα-dependent manner and regulates osteoclast differentiation and bone resorption. We thus provide evidence for a central role of autophagy in joint destruction in RA.
CRIS-Team Scopus Importer:2020-11-20

Case Report: Neutralization of Autoantibodies Targeting G-Protein-Coupled Receptors Improves Capillary Impairment and Fatigue Symptoms After COVID-19 Infection - Hohberger, Bettina; Harrer, Thomas; Mardin, Christian; Kruse, Friedrich; Hoffmanns, Jakob; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; Szewczykowski, Charlotte; Schottenhamml, Julia; Kräter, Martin; Bergua, Antonio; et al. (Frontiers in Medicine, 2021)
Clinical features of Coronavirus disease 2019 (COVID-19) are caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Acute infection management is a substantial healthcare issue, and the development of long-Covid syndrome (LCS) is extremely challenging for patients and physicians. It is associated with a variety of characteristics as impaired capillary microcirculation, chronic fatigue syndrome (CFS), proinflammatory cytokines, and functional autoantibodies targeting G-protein-coupled receptors (GPCR-AAbs). Here, we present a case report of successful healing of LCS with BC 007 (Berlin Cures, Berlin, Germany), a DNA aptamer drug with a high affinity to GPCR-AAbs that neutralizes these AAbs. A patient with a documented history of glaucoma, recovered from mild COVID-19, but still suffered from CFS, loss of taste, and impaired capillary microcirculation in the macula and peripapillary region. He was positively tested for various targeting GPCR-AAbs. Within 48 h after a single BC 007 treatment, GPCR-AAbs were functionally inactivated and remained inactive during the observation period of 4 weeks. This observation was accompanied by constant improvement of the fatigue symptoms of the patient, taste, and retinal capillary microcirculation. Therefore, the removal of GPCR-AAb might ameliorate the characteristics of the LCD, such as capillary impairment, loss of taste, and CFS.
CRIS-Team Scopus Importer:2021-12-17
Keywords: BC 007; chronic fatigue syndrome; COVID-19; functional GPCR autoantibodies; glaucoma; long-COVID syndrome; OCT angiography

Cell types and synapses expressing the snare complex regulating proteins complexin 1 and complexin 2 in mammalian retina - Lux, Uwe; Ehrenberg, Johanna; Joachimsthaler, Anneka; Atorf, Jenny; Pircher, Bianca; Reim, Kerstin; Kremers, Jan; Gießl, Andreas; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2021)
Complexins (Cplxs) 1 to 4 are components of the presynaptic compartment of chemical synapses where they regulate important steps in synaptic vesicle exocytosis. In the retina, all four Cplxs are present, and while we know a lot about Cplxs 3 and 4, little is known about Cplxs 1 and 2. Here, we performed in situ hybridization experiments and bioinformatics and exploited Cplx 1 and Cplx 2 single-knockout mice combined with immunocytochemistry and light microscopy to characterize in detail the cell type and synapse-specific distribution of Cplx 1 and Cplx 2. We found that Cplx 2 and not Cplx 1 is the main isoform expressed in normal and displaced amacrine cells and ganglion cells in mouse retinae and that amacrine cells seem to operate with a single Cplx isoform at their conventional chemical synapses. Surprising was the finding that retinal function, determined with electroretinographic recordings, was altered in Cplx 1 but not Cplx 2 single-knockout mice. In summary, the results provide an important basis for future studies on the function of Cplxs 1 and 2 in the processing of visual signals in the mammalian retina.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Amacrine cells; Complexin 1; Complexin 2; Conventional chemical synapses; Ganglion cells; Horizontal cells; Retina

CLL-Derived Extracellular Vesicles Impair T-Cell Activation and Foster T-Cell Exhaustion via Multiple Immunological Checkpoints - Boettcher, Martin; Boettcher-Loschinski, Romy; Kahlfuss, Sascha; Aigner, Michael; Gießl, Andreas; Mackensen, Andreas; Schlötzer-Schrehardt, Ursula; Tueting, Thomas; Bruns, Heiko; Mougiakakos, Dimitrios (Cells, 2022)
Background: Chronic lymphocytic leukemia (CLL) is characterized by the clonal expansion of malignant B-cells and multiple immune defects. This leads, among others, to severe infectious complications and inefficient immune surveillance. T-cell deficiencies in CLL include enhanced immune(-metabolic) exhaustion, impaired activation and cytokine production, and immunological synapse malformation. Several studies have meanwhile reported CLL-cell-T-cell interactions that culminate in T-cell dysfunction. However, the complex entirety of their interplay is incompletely understood. Here, we focused on the impact of CLL cell-derived vesicles (EVs), which are known to exert immunoregulatory effects, on T-cell function. Methods: We characterized EVs secreted by CLL-cells and determined their influence on T-cells in terms of survival, activation, (metabolic) fitness, and function. Results: We found that CLL-EVs hamper T-cell viability, proliferation, activation, and metabolism while fostering their exhaustion and formation of regulatory T-cell subsets. A detailed analysis of the CLL-EV cargo revealed an abundance of immunological checkpoints (ICs) that could explain the detected T-cell dysregulations. Conclusions: The identification of a variety of ICs loaded on CLL-EVs may account for T-cell defects in CLL patients and could represent a barrier for immunotherapies such as IC blockade or adoptive T-cell transfer. Our findings could pave way for improving antitumor immunity by simultaneously targeting EV formation or multiple ICs.
CRIS-Team Scopus Importer:2022-08-12
Keywords: cellular therapy; chronic lymphocytic leukemia; extracellular vesicles; immune checkpoints; immune evasion; T-cells

Die Blut-Augen-Schranken und ihre Störungen: Anatomie, Physiologie, Pathologie - Braunger, Barbara M.; Gießl, Andreas; Schlötzer-Schrehardt, Ursula (Klinische Monatsblätter für Augenheilkunde, 2023)
Complex barriers comprise the blood-aqueous (BAB) and the blood-retinal barrier (BRB), and separate anterior and posterior eye chambers, vitreous body, and sensory retina from the circulation. They prevent pathogens and toxins from entering the eye, control movement of fluid, proteins, and metabolites, and contribute to the maintenance of the ocular immune status. Morphological correlates of blood-ocular barriers are tight junctions between neighboring endothelial and epithelial cells, which function as gatekeepers of the paracellular transport of molecules, thereby limiting their uncontrolled access to ocular chambers and tissues. The BAB is composed of tight junctions between endothelial cells of the iris vasculature, endothelial cells of Schlemm's canal inner wall, and cells of the nonpigmented ciliary epithelium. The BRB consists of tight junctions between endothelial cells of the retinal vessels (inner BRB) and epithelial cells of the retinal pigment epithelium (outer BRB). These junctional complexes respond rapidly to pathophysiological changes, thus enabling vascular leakage of blood-derived molecules and inflammatory cells into ocular tissues and chambers. Blood-ocular barrier function, which can be clinically measured by laser flare photometry or fluorophotometry, is compromised in traumatic, inflammatory, or infectious processes, but also frequently contributes to the pathophysiology of chronic diseases of the anterior eye segment and the retina, as exemplified by diabetic retinopathy and age-related macular degeneration.
CRIS-Team Scopus Importer:2023-06-02

Drug- and Cell-Type-Specific Effects of ROCK Inhibitors as a Potential Cause of Reticular Corneal Epithelial Edema - Schlötzer-Schrehardt, Ursula; Gießl, Andreas; Zenkel, Matthias; Bartsch, Alexander; Okumura, Naoki; Koizumi, Noriko; Kinoshita, Shigeru; Tourtas, Theofilos; Kruse, Friedrich (Cells, 2025)
Rho-associated kinase (ROCK) inhibitors have gained popularity as novel treatment options in the management of glaucoma and corneal endothelial disorders. Among the various ocular side effects, reticular corneal epithelial edema has been most frequently reported, mainly after treatment with netarsudil. To explain the potential mechanisms, we comparatively analyzed the effects of ripasudil and netarsudil on corneal endothelial and epithelial function in vitro. Primary human corneal endothelial and epithelial cells were incubated with netarsudil dihydrochloride and ripasudil hydrochloride dihydrate for up to 7 days. Gene and protein expression analyses were performed by real-time PCR and immunocytochemistry. Functional assays assessed the cell migration, proliferation, viability, Na+/K+-ATPase activity, transcellular electrical resistance, and FITC–dextran permeability. Reticular bullous corneal epithelial edema was observed in a patient following netarsudil 0.02%/latanoprost 0.005% ophthalmic solution (Roclanda®) for elevated intraocular pressure. In the subsequent laboratory analyses, both netarsudil and ripasudil were found to improve the corneal endothelial pump and barrier function, but they showed differential effects on corneal epithelial cells. Whereas ripasudil improved the epithelial barrier function by upregulating major components of the tight and adherens junctions and reducing paracellular permeability, netarsudil had no or even adverse effects on the epithelial barrier properties by downregulating the expression levels of cell-junction-associated genes. The expression changes normalized after discontinuation of ROCK inhibitors. The findings support the concept that ROCK inhibitors can act as a double-edged sword by having beneficial effects on corneal endothelial cells and adverse effects on epithelial cells.
CRIS-Team Scopus Importer:2025-03-14
Keywords: corneal endothelium; corneal epithelium; honeycomb epithelial edema; netarsudil; reticular bullous corneal epithelial edema; Rho kinase inhibitor; ripasudil; ROCK inhibitor

DYNC2LI1 mutations broaden the clinical spectrum of dynein-2 defects - Keßler, Kristin; Wunderlich, Ina; Uebe, Steffen; Falk, Nathalie; Gießl, Andreas; Brandstätter, Johann Helmut; Popp, Bernt; Klinger, Patricia; Ekici, Arif Bülent; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Scientific Reports, 2015)
Skeletal ciliopathies are a heterogeneous group of autosomal recessive osteochondrodysplasias caused by defects in formation, maintenance and function of the primary cilium. Mutations in the underlying genes affect the molecular motors, intraflagellar transport complexes (IFT), or the basal body. The more severe phenotypes are caused by defects of genes of the dynein-2 complex, where mutations in DYNC2H1, WDR34 and WDR60 have been identified. In a patient with a Jeune-like phenotype we performed exome sequencing and identified compound heterozygous missense and nonsense mutations in DYNC2LI1 segregating with the phenotype. DYNC2LI1 is ubiquitously expressed and interacts with DYNC2H1 to form the dynein-2 complex important for retrograde IFT. Using DYNC2LI1 siRNA knockdown in fibroblasts we identified a significantly reduced cilia length proposed to affect cilia function. In addition, depletion of DYNC2LI1 induced altered cilia morphology with broadened ciliary tips and accumulation of IFT-B complex proteins in accordance with retrograde IFT defects. Our results expand the clinical spectrum of ciliopathies caused by defects of the dynein-2 complex.
EVALuna2:9281

Dysfunction of the limbal epithelial stem cell niche in aniridia-associated keratopathy: Limbal niche in aniridia-associated keratopathy - Schlötzer-Schrehardt, Ursula; Latta, Lorenz; Gießl, Andreas; Zenkel, Matthias; Fries, Fabian N.; Käsmann-Kellner, Barbara; Kruse, Friedrich; Seitz, Berthold (Ocular Surface, 2021)
Purpose: Abnormalities in the limbal niche microenvironment have been suggested to be causally involved in aniridia-associated keratopathy (AAK), but histological analyses on the limbal structure and composition in AAK are lacking. Here, we investigated morphologic and molecular alterations of the limbal epithelial stem cell niche in human congenital aniridia. Methods: The blind, buphthalmic and painful left eye of a 16-year old girl with congenital aniridia and juvenile glaucoma had to be enucleated because of uncontrolled intraocular pressure. The diagnosis of AAK was based on classical clinical features and partial limbal stem cell deficiency in the superior half. Genetic analysis identified a large heterozygous PAX6 gene deletion encompassing exons 11–15 as well as exon 9 of the neighboring ELP4 gene. Three limbal biopsies were taken from the superior, nasal and temporal regions to isolate and cultivate limbal epithelial progenitor cells and subject them to mRNA expression analyses. The globe was vertically bisected and processed for light and transmission electron microscopy and immunohistochemistry. Results: Comparative analysis of the superior and inferior limbal zones showed a gradual degradation of palisade structures associated with the transition from a hyperplastic to an attenuated corneal epithelium, inflammatory cell infiltrations and basement membrane irregularities. The clinically unaffected inferior part revealed no distinct stem cell clusters in the preserved palisade region, but a uniform population of hyperproliferative, undifferentiated progenitor cells in the basal/suprabasal layers of limbal and corneal epithelia, which gave rise to maldifferentiated epithelial cells exhibiting a conjunctival/epidermal phenotype and nuclear-to-cytoplasmic translocation of Pax6. The structure of the limbal niche was fundamentally perturbed, showing marked alterations in extracellular matrix composition, dislocation of atypical melanocytes lacking melanosomes and melanin, aberrant Wnt/β-catenin and retinoic acid signaling, and massive immune cell infiltration. Conclusions: Considering the limitations of a single Case study, the findings suggest that ocular surface alterations in AAK are caused by a primary dysfunction and gradual breakdown of the limbal stem cell niche through Pax6-related effects on both melanogenesis and epithelial differentiation.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Aniridia-associated keratopathy; Extracellular matrix; Immunohistochemistry; Limbal stem cell niche; Melanocytes; Pax6

Dysregulated Retinoic Acid Signaling in the Pathogenesis of Pseudoexfoliation Syndrome - Zenkel, Matthias; Hoja, Ursula; Gießl, Andreas; Berner, Daniel; Hohberger, Bettina; Weller, Julia; König, Loretta; Huebner, Lisa; Ostermann, Thomas A.; Gusek-Schneider, Gabriele; Kruse, Friedrich; Pasutto, Francesca; et al. (International Journal of Molecular Sciences, 2022)
Pseudoexfoliation (PEX) syndrome, a stress-induced fibrotic matrix process, is the most common recognizable cause of open-angle glaucoma worldwide. The recent identification of PEX-associated gene variants uncovered the vitamin A metabolic pathway as a factor influencing the risk of disease. In this study, we analyzed the role of the retinoic acid (RA) signaling pathway in the PEX-associated matrix metabolism and evaluated its targeting as a potential candidate for an anti-fibrotic intervention. We provided evidence that decreased expression levels of RA pathway components and diminished RA signaling activity occur in an antagonistic crosstalk with TGF-beta 1/Smad signaling in ocular tissues and cells from PEX patients when compared with age-matched controls. Genetic and pharmacologic modes of RA pathway inhibition induced the expression and production of PEX-associated matrix components by disease-relevant cell culture models in vitro. Conversely, RA signaling pathway activation by natural and synthetic retinoids was able to suppress PEX-associated matrix production and formation of microfibrillar networks via antagonization of Smad-dependent TGF-beta 1 signaling. The findings indicate that deficient RA signaling in conjunction with hyperactivated TGF-beta 1 /Smad signaling is a driver of PEX-associated fibrosis, and that restoration of RA signaling may be a promising strategy for anti-fibrotic intervention in patients with PEX syndrome and glaucoma.
CRIS-Team WoS Importer:2022-06-24
Keywords: pseudoexfoliation syndrome; pseudoexfoliation glaucoma; retinol; retinoic acid; extracellular matrix; fibrosis; TGF-β1

Effective isolation and expansion of human limbal niche cells - Gießl, Andreas; Polisetti, Naresh; Li, Shen; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Enrichment, Characterization, and Proteomic Profiling of Small Extracellular Vesicles Derived from Human Limbal Mesenchymal Stromal Cells and Melanocytes - Kistenmacher, Sebastian; Schwämmle, Melanie; Martin, Gottfried; Ulrich, Eva; Tholen, Stefan; Schilling, Oliver; Gießl, Andreas; Schlötzer-Schrehardt, Ursula; Bucher, Felicitas; Schlunck, Günther; Nazarenko, Irina; Reinhard, Thomas; et al. (Cells, 2024)
Limbal epithelial progenitor cells (LEPC) rely on their niche environment for proper functionality and self-renewal. While extracellular vesicles (EV), specifically small EVs (sEV), have been proposed to support LEPC homeostasis, data on sEV derived from limbal niche cells like limbal mesenchymal stromal cells (LMSC) remain limited, and there are no studies on sEVs from limbal melanocytes (LM). In this study, we isolated sEV from conditioned media of LMSC and LM using a combination of tangential flow filtration and size exclusion chromatography and characterized them by nanoparticle tracking analysis, transmission electron microscopy, Western blot, multiplex bead arrays, and quantitative mass spectrometry. The internalization of sEV by LEPC was studied using flow cytometry and confocal microscopy. The isolated sEVs exhibited typical EV characteristics, including cell-specific markers such as CD90 for LMSC-sEV and Melan-A for LM-sEV. Bioinformatics analysis of the proteomic data suggested a significant role of sEVs in extracellular matrix deposition, with LMSC-derived sEV containing proteins involved in collagen remodeling and cell matrix adhesion, whereas LM-sEV proteins were implicated in other cellular bioprocesses such as cellular pigmentation and development. Moreover, fluorescently labeled LMSC-sEV and LM-sEV were taken up by LEPC and localized to their perinuclear compartment. These findings provide valuable insights into the complex role of sEV from niche cells in regulating the human limbal stem cell niche.
CRIS-Team Scopus Importer:2024-04-26
Keywords: exosomes; extracellular vesicles; limbal epithelial progenitor cells; limbal melanocytes; limbal mesenchymal stromal cells; limbal stem cell niche; proteomics

Epithelial HIF2 alpha expression induces intestinal barrier dysfunction and exacerbation of arthritis - Wen, Jinming; Lyu, Pang; Stolzer, Iris; Xu, Jin; Gießl, Andreas; Lin, Zhen; Andreev, Darja; Kachler, Katerina; Song, Rui; Meng, Xianyi; Cao, Shan; Guggino, Giuliana; et al. (Annals of the Rheumatic Diseases, 2022)
To investigate how the mucosal barrier in the intestine influences the development of arthritis, considering that metabolic changes in the intestinal epithelium influence its barrier function. Intestinal HIF2α expression peaked at onset of experimental arthritis and RA. Conditionally, deletion of HIF2α in gut epithelial cells inhibited arthritis and was associated with improved intestinal barrier function and less intestinal and lymphatic Th1 and Th17 activation. Mechanistically, HIF2α induced the transcription of the pore-forming claudin (CLDN)-15, which inhibits intestinal barrier integrity. Furthermore, treatment with HIF2α inhibitor decreased claudin-15 expression in epithelial cells and inhibited arthritis and littermate control mice. The gut intestinal HIF2α target genes were delineated by chromatin immunoprecipitation and luciferase experiments. Furthermore, pharmacological HIF2α inhibitor PT2977 was used for inhibition of arthritis. These findings show that the HIF2α-CLDN15 axis is critical for the breakdown of intestinal barrier function at onset of arthritis, highlighting the functional link between intestinal homeostasis and arthritis.
CRIS-Team WoS Importer:2022-07-01
Keywords: Arthritis; Arthritis; Experimental; Inflammation.

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Exosomal ROR1 in peritoneal fluid identifies peritoneal disseminated PDAC and is associated with poor survival - Mittelstädt, Anke; Anthuber, Anna; David, Paul; Podolska, Malgorzata; Benard, Alan; Brunner, Maximilian; Krautz, Christian; Jacobsen, Anne; Denz, Axel; Weber, Klaus; Merkel, Susanne; Hackner, Danilo; et al. (Frontiers in Immunology, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer and peritoneal dissemination is one major cause for this poor prognosis. Exosomes have emerged as promising biomarkers for gastrointestinal cancers and can be found in all kinds of bodily fluids, also in peritoneal fluid (PF). This is a unique sample due to its closeness to gastrointestinal malignancies. The receptor tyrosine kinase-like orphan receptor 1 (ROR1) has been identified as a potential biomarker in human cancers and represents a promising target for an immunotherapy approach, which could be considered for future treatment strategies. Here we prospectively analyzed the exosomal surface protein ROR1 (exo-ROR1) in PF in localized PDAC patients (PER-) on the one hand and peritoneal disseminated tumor stages (PER+) on the other hand followed by the correlation of exo-ROR1 with clinical-pathological parameters. Methods: Exosomes were isolated from PF and plasma samples of non-cancerous (NC) (n = 15), chronic pancreatitis (CP) (n = 4), localized PDAC (PER-) (n = 18) and peritoneal disseminated PDAC (PER+) (n = 9) patients and the surface protein ROR1 was detected via FACS analysis. Additionally, soluble ROR1 in PF was analyzed. ROR1 expression in tissue was investigated using western blots (WB), qPCR, and immunohistochemistry (IHC). Exosome isolation was proven by Nano Tracking Analysis (NTA), WB, Transmission electron microscopy (TEM), and BCA protein assay. The results were correlated with clinical data and survival analysis was performed. Results: PDAC (PER+) patients have the highest exo-ROR1 values in PF and can be discriminated from NC (p <0.0001), PDAC (PER-) (p <0.0001), and CP (p = 0.0112). PDAC (PER-) can be discriminated from NC (p = 0.0003). In plasma, exo-ROR1 is not able to distinguish between the groups. While there is no expression of ROR1 in the exocrine pancreatic tissue, PDAC and peritoneal metastasis show expression of ROR1. High exo-ROR1 expression in PF is associated with lower overall survival (p = 0.0482). Conclusion: With exo-ROR1 in PF we found a promising diagnostic and prognostic biomarker possibly discriminating between NC, PDAC (PER-) and PDAC (PER+) and might shed light on future diagnostic and therapeutic concepts in PDAC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: biomarker; exosomes; PDAC; peritoneal carcinomatosis; peritoneal fluid; peritoneal lavage; ROR1; targeted therapy

Expression of HIF1α in intestinal epithelium restricts arthritis inflammation by inhibiting RIPK3-induced cell death machinery - Lyu, Pang; Wen, Jinming; Zhang, Wenshuo; Liu, Ning; Stolzer, Iris; Gießl, Andreas; Jia, Yewei; Mauro, Daniele; Zhang, Fulin; Ciccia, Francesco; Soulat, Didier; Günther, Claudia; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: To investigate the mechanism by which intestinal epithelial cell (IEC) death induces arthritis. Methods: IEC death was assessed by staining for necroptosis and apoptosis markers and fluorescence in situ hybridisation at different time points during collagen-induced arthritis (CIA). During the development of CIA, messenger RNA (mRNA) sequencing was performed, followed by Gene Ontology enrichment analysis of differentially expressed genes. Mice deficient for hypoxia-inducible factor 1α (Hif1a) in IECs (Hif1aΔIEC) were generated and induced for arthritis. mRNA sequencing, chromatin immunoprecipitated (ChIP) DNA sequencing and ChIP-qualitative PCR were performed on IECs from Hif1aΔIEC mice and littermate controls. Effects of HIF1α stabilisation by inhibition of prolyl hydroxylase domain-containing enzymes and treatment with the inhibitor of receptor-interacting protein kinase-3 (RIPK3) were tested in intestinal organoids and in CIA. Results: IEC underwent apoptotic and necroptotic cell death at the onset of arthritis, leading to impaired gut barrier function. HIF1α was identified as one of the most upregulated genes in IECs during the onset of arthritis. Deletion of Hif1a in IEC enhanced IEC necroptosis, triggered intestinal inflammation and exacerbated arthritis. HIF1α was found to be a key transcriptional repressor for the necroptosis-inducing factor RIPK3. Enhanced RIPK3 expression, indicating necroptosis, was also found in the intestinal epithelium of patients with new-onset rheumatoid arthritis. Therapeutic stabilisation of HIF1α as well as small-molecule-based RIPK3 inhibition rescued intestinal necroptosis in vitro and in vivo and suppressed the development of arthritis. Conclusion: Our results identify IEC necroptosis as a critical link between the gut and the development of arthritis.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Immune System Diseases; Inflammation

Extracellular Vesicles of CLL Cells affect T-Cell Activation and promote their Depletion via diverse immunological Checkpoints - Boettcher, M.; Boettcher-Loschinski, R.; Gießl, Andreas; Schlötzer-Schrehardt, Ursula; Bruns, Heiko; Mougiakakos, D. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Functional analyses of Pericentrin and Syne-2 interaction in ciliogenesis - Falk, Nathalie; Keßler, Kristin; Schramm, Sinja-Fee; Boldt, Karsten; Becirovic, Elvir; Michalakis, Stylianos; Regus-Leidig, Hanna; Noegel, Angelika A.; Ueffing, Marius; Thiel, Christian; Roepman, Ronald; Brandstätter, Johann Helmut; et al. (Journal of Cell Science, 2018)
Pericentrin (Pcnt) is a multifunctional scaffold protein and mutations in the human PCNT gene are associated with several diseases, including ciliopathies. Pcnt plays a crucial role in ciliary development in olfactory receptor neurons, but its function in the photoreceptor-connecting cilium is unknown. We downregulated Pcnt in the retina ex vivo and in vivo via a virus-based RNA interference approach to study Pcnt function in photoreceptors. ShRNA-mediated knockdown of Pcnt impaired the development of the connecting cilium and the outer segment of photoreceptors, and caused a nuclear migration defect. In protein interaction screens, we found that the outer nuclear membrane protein Syne-2 (also known as Nesprin-2) is an interaction partner of Pcnt in photoreceptors. Syne-2 is important for positioning murine photoreceptor cell nuclei and for centrosomal migration during early ciliogenesis. CRISPR/Cas9-mediated knockout of Syne-2 in cell culture led to an overexpression and mislocalization of Pcnt and to ciliogenesis defects. Our findings suggest that the Pcnt-Syne-2 complex is important for ciliogenesis and outer segment formation during retinal development and plays a role in nuclear migration.
EVALuna2:34620

Histological aspects of limbal stem cell transplantation - Gießl, Andreas (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

Identification and characterisation of Simiate, a novel protein linked to the fragile X syndrome - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (PLoS ONE, 2013)
A strict regulation of protein expression during developmental stages and in response to environmental signals is essential to every cell and organism. Recent research has shown that the mammalian brain is particularly sensitive to alterations in expression patterns of specific proteins and cognitive deficits as well as autistic behaviours have been linked to dysregulated protein expression. An intellectual disability characterised by changes in the expression of a variety of proteins is the fragile X syndrome. Due to the loss of a single mRNA binding protein, the Fragile X Mental Retardation Protein FMRP, vast misregulation of the mRNA metabolism is taking place in the disease. Here, we present the identification and characterisation of a novel protein named Simiate, whose mRNA contains several FMRP recognition motifs and associates with FMRP upon co-precipitation. Sequence analysis revealed that the protein evolved app. 1.7 billion years ago when eukaryotes developed. Applying antibodies generated against Simiate, the protein is detected in a variety of tissues, including the mammalian brain. On the subcellular level, Simiate localises to somata and nuclear speckles. We show that Simiate and nuclear speckles experience specific alterations in FMR1(-/-) mice. An antibody-based block of endogenous Simiate revealed that the protein is essential for cell survival. These findings suggest not only an important role for Simiate in gene transcription and/or RNA splicing, but also provide evidence for a function of nuclear speckles in the fragile X syndrome. Indeed, transcription and splicing are two fundamental mechanisms to control protein expression, that underlie not only synaptic plasticity and memory formation, but are also affected in several diseases associated with mental disabilities.
EVALuna2:4700

Identification, Isolation, and Characterization of Melanocyte Precursor Cells in the Human Limbal Stroma - Li, Shen; Zenkel, Matthias; Kruse, Friedrich; Gießl, Andreas; Schlötzer-Schrehardt, Ursula (International Journal of Molecular Sciences, 2022)
Given their vital role in the homeostasis of the limbal stem cell niche, limbal melanocytes have emerged as promising candidates for tissue engineering applications. This study aimed to isolate and characterize a population of melanocyte precursors in the limbal stroma, compared with melanocytes originating from the limbal epithelium, using magnetic-activated cell sorting (MACS) with positive (CD117/c-Kit microbeads) or negative (CD326/EpCAM or anti-fibroblast microbeads) selection approaches. Both approaches enabled fast and easy isolation and cultivation of pure limbal epithelial and stromal melanocyte populations, which differed in phenotype and gene expression, but exhibited similar functional properties regarding proliferative potential, pigmentation, and support of clonal growth of limbal epithelial stem/progenitor cells (LEPCs). In both melanocyte populations, limbus-specific matrix (laminin 511-E8) and soluble factors (LEPC-derived conditioned medium) stimulated melanocyte adhesion, dendrite formation, melanogenesis, and expression of genes involved in UV protection and immune regulation. The findings provided not only a novel protocol for the enrichment of pure melanocyte populations from limbal tissue applying easy-to-use MACS technology, but also identified a population of stromal melanocyte precursors, which may serve as a reservoir for the replacement of damaged epithelial melanocytes and an alternative resource for tissue engineering applications.
CRIS-Team Scopus Importer:2022-04-15
Keywords: cultivation; laminin 511-E8; limbal stem cell niche; limbal stem cells; limbal stroma; magnetic-activated cell sorting; melanocytes

Identification of the deregulated NEK1 protein network in skeletal ciliopathies - Vogl, C.; Keßler, Kristin; Gießl, Andreas; Kirchner, P.; Büttner, Christian; Ekici, Arif Bülent; Reis, André; Thiel, C. T. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Impaired Mitochondrial Transcription Factor A Expression Promotes Mitochondrial Damage to Drive Fibroblast Activation and Fibrosis in Systemic Sclerosis - Zhou, Xiang; Trinh, Minh Thuong; Tran Manh, Cuong; Gießl, Andreas; Bergmann, Christina; Györfi, Andrea-Hermina; Schett, Georg; Distler, Jörg (Arthritis and Rheumatology, 2022)
Objective Mitochondrial transcription factor A (TFAM) controls the transcription of core proteins required for mitochondrial homeostasis. This study was undertaken to investigate changes in TFAM expression in systemic sclerosis (SSc), to analyze mitochondrial function, and to evaluate the consequences for fibroblast activation. Methods TFAM expression was analyzed by immunofluorescence and Western blotting. The effects of TFAM knockout were investigated in cultured fibroblasts and in murine models of bleomycin-induced skin fibrosis, bleomycin-induced lung fibrosis, and skin fibrosis induced by overexpression of constitutively active transforming growth factor beta type I receptor (TGF beta R Iota). Results TFAM expression was down-regulated in fibroblasts in SSc skin and in cultured SSc fibroblasts. The down-regulation of TFAM was associated with decreased mitochondrial number and accumulation of damaged mitochondria with release of mitochondrial DNA (mtDNA), accumulation of deletions in mtDNA, metabolic alterations with impaired oxidative phosphorylation, and release of the mitokine GDF15. Normal fibroblasts subjected to long-term, but not acute, exposure to TGF beta mimicked SSc fibroblasts, with down-regulation of TFAM and accumulation of mitochondrial damage. Down-regulation of TFAM promoted fibroblast activation with up-regulation of fibrosis-relevant Gene Ontology terms in RNA-Seq, partially in a reactive oxygen species-dependent manner. Mice with fibroblast-specific knockout of Tfam were prone to fibrotic tissue remodeling, with fibrotic responses even to NaCl instillation and enhanced sensitivity to bleomycin injection and overexpression of constitutively active TGF beta RI. TFAM knockout fostered Smad3 signaling to promote fibroblast activation. Conclusion Alterations in the key mitochondrial transcription factor TFAM in response to prolonged activation of TGF beta and associated mitochondrial damage induce transcriptional programs that promote fibroblast-to-myofibroblast transition and drive tissue fibrosis.
CRIS-Team WoS Importer:2022-04-15

Interferometric scattering microscopy reveals microsecond nanoscopic protein motion on a live cell membrane - Taylor, Richard W.; Mahmoodabadi, Reza Gholami; Rauschenberger, Verena; Gießl, Andreas; Schambony, Alexandra; Sandoghdar, Vahid (Nature Photonics, 2019)
Many of the biological functions of a cell are dictated by the intricate motion of proteins within its membrane over a spatial range of nanometres to tens of micrometres and time intervals of microseconds to minutes. This rich parameter space is not accessible by fluorescence microscopy, but it is within reach of interferometric scattering (iSCAT) particle tracking. However, as iSCAT is sensitive even to single unlabelled proteins, it is often accompanied by a large speckle-like background, which poses a substantial challenge for its application to cellular imaging. Here, we employ a new image processing approach to overcome this difficulty and demonstrate tracking of transmembrane epidermal growth factor receptors with nanometre precision in all three dimensions at up to microsecond speeds and for durations of tens of minutes. We provide examples of nanoscale motion and confinement in ubiquitous processes such as diffusion in the plasma membrane, transport on filopodia and rotational motion during endocytosis.
CRIS-Team Scopus Importer:2019-05-02

INTESTINAL HIF1 alpha EXPRESSION PROTECTS AGAINST EPITHELIAL CELL DEATH IN ARTHRITIS - Lyu, Pang; Wen, Jinming; Stolzer, Iris; Gießl, Andreas; Song, Rui; Meng, Xiangjun; Cao, Shan; Günther, Claudia; Schett, Georg; Bozec, Aline (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Lack of a Retinal Phenotype in a Syne-2/Nesprin-2 Knockout Mouse Model - Falk, Nathalie; Joachimsthaler, Anneka; Keßler, Kristin; Lux, Uwe; Noegel, Angelika Anna; Kremers, Jan; Brandstätter, Johann Helmut; Gießl, Andreas (Cells, 2019)
Syne-2 (also known as Nesprin-2) is a member of a family of proteins that are found primarily in the outer nuclear membrane, as well as other subcellular compartments. Syne-2 contains a C-terminal KASH transmembrane domain and is part of a protein network that associates the nuclear envelope to the cytoskeleton via the binding to actin filaments. Syne-2 plays a role in nuclear migration, nuclear positioning during retinal development, and in ciliogenesis. In a previous study, we showed a connection between Syne-2 and the multifunctional scaffold protein Pericentrin (Pcnt). The elimination of the interaction of Syne-2 and Pcnt showed defects in nuclear migration and the formation of outer segments during retinal development, as well as disturbances in centrosomal migration at the beginning of ciliogenesis in general. In this study, the Syne-2 KO mouse model Nesprin-2oABD (Syne-2(tm1Ngl), MGI) with special attention to Pcnt and ciliogenesis was analyzed. We show reduced expression of Syne-2 in the retina of the Syne-2 KO mouse but found no significant structural-and only a minor functional-phenotype. For the first time, detailed expression analyses showed an expression of a Syne-2 protein larger than 400 kDa (similar to 750 kDa) in the Syne-2/Nesprin-2 KO mouse. In conclusion, the lack of an overt phenotype in Syne-2/Nesprin-2 KO mice suggests the usage of alternative translational start sites, producing Syne-2 splice variants with an intact Pcnt interaction site. Nevertheless, deletion of the actin-binding site in the Syne-2/Nesprin-2 KO mouse revealed a high variability in scotopic oscillatory potentials assuming a novel function of Syne-2 in synchronizing inner retinal processes.
CRIS-Team WoS Importer:2019-11-29

Laminin-511-E8 promotes efficient in vitro expansion of human limbal melanocytes - Polisetti, Naresh; Gießl, Andreas; Li, Shen; Sorokin, Lydia; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Scientific Reports, 2020)
Limbal melanocytes, located in the basal epithelial layer of the corneoscleral limbus, represent essential components of the corneal epithelial stem cell niche, but, due to difficulties in their isolation and cultivation, their biological roles and potential for stem cell-based tissue engineering approaches have not been comprehensively studied. Here, we established a protocol for the efficient isolation and cultivation of pure populations of human limbal melanocytes, which could be expanded at high yield by using recombinant laminin (LN)-511-E8 as culture substrate. Co-cultivation of limbal melanocytes with limbal epithelial stem/progenitor cells on fibrin hydrogels pre-incubated with LN-511-E8 resulted in multilayered stratified epithelial constructs within ten days. By reproducing physiological cell–cell and cell–matrix interactions of the native niche environment, these biomimetic co-culture systems provide a promising experimental model for investigating the functional roles of melanocytes in the limbal stem cell niche and their suitability for developing advanced epithelial grafts for ocular surface surface reconstruction.
CRIS-Team Scopus Importer:2020-07-17

Light-dependent regulation of neurotransmitter release from rod photoreceptor ribbon synapses involves an interplay of Complexin 4 and Transducin with the SNARE complex - Lux, Uwe; Meyer, Jutta; Jahn, Olaf; Davison, Adam; Babai, Norbert; Gießl, Andreas; Wartenberg, Anna; Sticht, Heinrich; Brose, Nils; Reim, Kerstin; Brandstätter, Johann Helmut (Frontiers in Molecular Neuroscience, 2024)
Adaptation of photoreceptor sensitivity to varying light intensities is a fundamental requirement for retinal function and vision. Adaptive mechanisms in signal transduction are well described, but little is known about the mechanisms that adapt the photoreceptor synapse to changing light intensities. The SNARE complex regulators Complexin 3 and Complexin 4 have been proposed to be involved in synaptic light adaptation by limiting synaptic vesicle recruitment and fusion. How this Complexin effect is exerted is unknown. Focusing on rod photoreceptors, we established Complexin 4 as the predominant Complexin in the light-dependent regulation of neurotransmitter release. The number of readily releasable synaptic vesicles is significantly smaller in light than in dark at wildtype compared to Complexin 4 deficient rod photoreceptor ribbon synapses. Electrophysiology indicates that Complexin 4 reduces or clamps Ca2+-dependent sustained synaptic vesicle release, thereby enhancing light signaling at the synapse. Complexin 4 deficiency increased synaptic vesicle release and desensitized light signaling. In a quantitative proteomic screen, we identified Transducin as an interactor of the Complexin 4-SNARE complex. Our results provide evidence for a presynaptic interplay of both Complexin 4 and Transducin with the SNARE complex, an interplay that may facilitate the adaptation of synaptic transmission to light at rod photoreceptor ribbon synapses.
CRIS-Team Scopus Importer:2024-04-05
Keywords: G protein; light adaptation; mouse retina; neurotransmitter release; ribbon synapses; rod photoreceptor

Long COVID: Association of Functional Autoantibodies against G-Protein-Coupled Receptors with an Impaired Retinal Microcirculation - Szewczykowski, Charlotte; Mardin, Christian; Lucio, Marianna; Wallukat, Gerd; Hoffmanns, Jakob; Schröder, Tim; Raith, Franziska; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; Beitlich, Lorenz; Schottenhamml, Julia; et al. (International Journal of Molecular Sciences, 2022)
Long COVID (LC) describes the clinical phenotype of symptoms after infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Diagnostic and therapeutic options are limited, as the pathomechanism of LC is elusive. As the number of acute SARS-CoV-2 infections was and is large, LC will be a challenge for the healthcare system. Previous studies revealed an impaired blood flow, the formation of microclots, and autoimmune mechanisms as potential factors in this complex interplay. Since functionally active autoantibodies against G-protein-coupled receptors (GPCR-AAbs) were observed in patients after SARS-CoV-2 infection, this study aimed to correlate the appearance of GPCR-AAbs with capillary microcirculation. The seropositivity of GPCR-AAbs was measured by an established cardiomyocyte bioassay in 42 patients with LC and 6 controls. Retinal microcirculation was measured by OCT–angiography and quantified as macula and peripapillary vessel density (VD) by the Erlangen-Angio Tool. A statistical analysis yielded impaired VD in patients with LC compared to the controls, which was accentuated in female persons. A significant decrease in macula and peripapillary VD for AAbs targeting adrenergic β2-receptor, MAS-receptor angiotensin-II-type-1 receptor, and adrenergic α1-receptor were observed. The present study might suggest that a seropositivity of GPCR-AAbs can be linked to an impaired retinal capillary microcirculation, potentially mirroring the systemic microcirculation with consecutive clinical symptoms.
CRIS-Team Scopus Importer:2022-07-15
Keywords: chronic fatigue syndrome; COVID-19; functionally GPCR autoantibodies; glaucoma; Long-COVID syndrome; OCT–angiography

MAP4-dependent regulation of microtubule formation affects centrosome, cilia, and golgi architecture as a central mechanism in growth regulation - Zahnleiter, Diana; Hauer, Nadine; Keßler, Kristin; Uebe, Steffen; Sugano, Yuya; Neuhauss, Stephan C. F.; Gießl, Andreas; Ekici, Arif Bülent; Blessing, Holger; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Human Mutation, 2015)
Numerous genes are involved in human growth regulation. Recently, autosomal-recessive inherited variants in centrosomal proteins have been identified in Seckel syndrome, primary microcephaly, or microcephalic osteodysplastic primary dwarfism. Common hallmarks of these syndromic forms are severe short stature and microcephaly. In a consanguineous family with two affected children with severe growth retardation and normocephaly, we used homozygosity mapping and next-generation sequencing to identify a homozygous MAP4 variant. MAP4 is a major protein for microtubule assembly during mitosis. High-expression levels in the somite boundaries of zebrafish suggested a role in growth and body segment patterning. The identified variant affects binding sites of kinases necessary for dynamic instability of microtubule formation. We found centrosome amplifications in mitotic fibroblast cells in vivo and in vitro. These numeric centrosomal aberrations were also present during interphase resulting in aberrant ciliogenesis. Furthermore, affected cells showed a dysfunction of the microtubule-dependent assembly of the Golgi apparatus, indicated by a significant lack of compactness of Golgi membranes. These observations demonstrated that MAP4 mutations contribute to the clinical spectrum of centrosomal defects and confirmed the complex role of a centrosomal protein in centrosomal, ciliary, and Golgi regulation associated with severe short stature.
EVALuna2:9244

Melanocytes as emerging key players in niche regulation of limbal epithelial stem cells - Polisetti, Naresh; Gießl, Andreas; Zenkel, Matthias; Heger, Lukas; Dudziak, Diana; Naschberger, Elisabeth; Stich, Lena; Steinkasserer, Alexander; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Ocular Surface, 2021)
Purpose: Limbal melanocytes (LMel) represent essential components of the corneal epithelial stem cell niche and are known to protect limbal epithelial stem/progenitor cells (LEPCs) from UV damage by transfer of melanosomes. Here, we explored additional functional roles for LMel in niche homeostasis, immune regulation and angiostasis. Methods: Human corneoscleral tissues were morphologically analyzed in normal, inflammatory and wound healing conditions. The effects of LMel on LEPCs were analyzed in direct and indirect co-culture models using electron microscopy, immunocytochemistry, qRT-PCR, Western blotting and functional assays; limbal mesenchymal stromal cells and murine embryonic 3T3 fibroblasts served as controls. The immunophenotype of LMel was assessed by flow cytometry before and after interferon-γ stimulation, and their immunomodulatory properties were analyzed by mixed lymphocytes reaction, monocyte adhesion assays and cytometric bead arrays. Their angiostatic effects on human umbilical cord endothelial cells (HUVECs) were evaluated by proliferation, migration, and tube formation assays. Results: LMel and LEPCs formed structural units in the human limbal stem cell niche in situ, which could be functionally replicated, including melanosome transfer, by co-cultivation in vitro. LMel supported LEPCs during clonal expansion and during epithelial wound healing by stimulating proliferation and migration, and suppressed their differentiation through direct contact and paracrine effects. Under inflammatory conditions, LMel were increased in numbers and upregulated expression of ICAM-1 and MHC II molecules (HLA-DR), but lacked expression of HLA-G, -DP, -DQ and costimulatory molecules CD80 and CD86. They were also found to be potent suppressors of alloreactive T- cell proliferation and cytokine secretion, which largely depended on direct cell-cell interaction. Moreover, the LMel secretome exerted angiostatic activity by inhibiting vascular endothelial cell proliferation and capillary network formation. Conclusion: These findings suggest that LMel are not only professional melanin-producing cells, but exert various non-canonical functions in limbal niche homeostasis by regulating LEPC maintenance, immune responses, and angiostasis. Their potent regulatory, immunomodulatory and anti-angiogenic properties may have important implications for future regenerative cell therapies.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Angiostasis; Immune regulation; Inflammation; Limbal niche; Limbal stem cells; Melanocytes; Wound healing

Mitochondrial metabolism contributes to oxidative stress and reveals therapeutic targets in chronic lymphocytic leukemia - Jitschin, Regina; Hofmann, Andreas D.; Bruns, Heiko; Gießl, Andreas; Bricks, Juliane; Berger, Jana; Saul, Domenica; Eckart, Michael J.; Mackensen, Andreas; Mougiakakos, Dimitrios (Blood, 2014)
Alterations of cellular metabolism represent a hallmark of cancer. Numerous metabolic changes are required for malignant transformation, and they render malignant cells more prone to disturbances in the metabolic framework. Despite the high incidence of chronic lymphocytic leukemia (CLL), metabolism of CLL cells remains a relatively unexplored area. The examined untreated CLL patients displayed a metabolic condition known as oxidative stress, which was linked to alterations in their lymphoid compartment. Our studies identified mitochondrial metabolism as the key source for abundant reactive oxygen species (ROS). Unlike in other malignant cells, we found increased oxidative phosphorylation in CLL cells but not increased aerobic glycolysis. Furthermore, CLL cells adapted to intrinsic oxidative stress by upregulating the stress-responsive heme-oxygenase-1 (HO-1). Our data implicate that HO-1 was, beyond its function as an antioxidant, involved in promoting mitochondrial biogenesis. Thus ROS, adaptation to ROS, and mitochondrial biogenesis appear to form a self-amplifying feedback loop in CLL cells. Taking advantage of the altered metabolic profile, we were able to selectively target CLL cells by PK11195. This benzodiazepine derivate blocks the mitochondrial F1F0-ATPase, leads to a surplus production of mitochondrial superoxide, and thereby induces cell death in CLL cells. Taken together, our findings depict how bioenergetics and redox characteristics could be therapeutically exploited in CL
EVALuna2:25687

Potential Functional Restoration of Corneal Endothelial Cells in Fuchs Endothelial Corneal Dystrophy by ROCK Inhibitor (Ripasudil) - Schlötzer-Schrehardt, Ursula; Zenkel, Matthias; Strunz, Maria; Gießl, Andreas; Schondorf, Hannah; da Silva, Heather; Schmidt, Gregory A.; Greiner, Mark A.; Okumura, Naoki; Koizumi, Noriko; Kinoshita, Shigeru; Tourtas, Theofilos; et al. (American Journal of Ophthalmology, 2021)
Purpose: Rho-associated kinase (ROCK) inhibitors have been successfully used as a rescue strategy in eyes that failed to clear after descemetorhexis without endothelial graft for treatment of Fuchs endothelial corneal dystrophy (FECD). The functional mechanisms by which ROCK inhibitors modulate corneal endothelial cell regeneration in FECD patients have, however, not been clarified. Here, we analyzed the effect of the ROCK inhibitor ripasudil on corneal endothelial cells of FECD patients and normal donors using ex vivo tissue and in vitro cellular models. Design: Experimental study: laboratory investigation. Methods: This institutional study used endothelial cell–Descemet membrane lamellae from FECD patients (n = 450) undergoing Descemet membrane endothelial keratoplasty (FECD ex vivo model), normal research-grade donor corneas (n = 30) after scraping off central endothelial cells (ex vivo wound healing model), normal donor corneas (n = 20) without endothelial injury, and immortalized cell lines (n = 3) generated from FECD patients (FECD in vitro model). Descemet membrane lamellae were dissected into halves and incubated for 24-72 hours in storage medium with or without a single dose of 30 μM ripasudil. The effects of ripasudil on expression of genes and proteins related to endothelial cell proliferation, migration, functionality, and endothelial-to-mesenchymal transition were analyzed and complemented by functional assays on FECD cell lines. Results: A single dose of ripasudil induced significant upregulation of genes and proteins related to cell cycle progression, cell-matrix adhesion and migration, as well as endothelial barrier and pump function up to 72 hours, whereas classical markers of endothelial-to-mesenchymal transition were downregulated in both FECD and normal specimens compared to unstimulated controls ex vivo. In addition to stimulation of proliferation and migration, ripasudil-induced changes in expression of functional signature genes could be also verified in FECD cell lines in vitro. Conclusions: These data support the concept that inhibition of ROCK signaling represents a potent tool in regenerative therapies in FECD patients through reactivation of cell proliferation and migration as well as restoration of endothelial pump and barrier function without inducing adverse phenotypic changes.
CRIS-Team Scopus Importer:2021-02-12

Proteomic Insights into Human Limbal Epithelial Progenitor-Derived Small Extracellular Vesicles - Braunsperger, Moritz Vincent; Martin, Gottfried; Herzig, Tabea; Kußberger, Isabell; Gießl, Andreas; Steimle, Stefan; Schlötzer-Schrehardt, Ursula; Schlunck, Günther; Reinhard, Thomas; Polisetti, Naresh (Stem Cell Reviews and Reports, 2025)
Limbal epithelial stem/progenitor cells (LEPC), supported by limbal mesenchymal stromal cells (LMSC) and limbal melanocytes (LM) within a specialized niche, are responsible for maintaining the corneal epithelium. Small extracellular vesicles (sEV) emerged as critical mediators of intercellular communication in various stem cell niches, yet their role in maintaining human limbal niche homeostasis remains poorly understood. In this study, tangential flow filtration and size exclusion chromatography were used to isolate sEV from LEPC-, LMSC- and LM-conditioned media. The isolated sEV from LEPC exhibited properties characteristic for sEV as confirmed by nanoparticle tracking analysis for size and concentration, by electron microscopy for morphology, and by western blot analysis of canonical EV markers including the cell-specific protein (cytokeratin 17/19). Quantitative and comparative proteomic profiling revealed distinct molecular signatures of LEPC-derived sEV, enriched in factors associated with keratinocyte development, extracellular matrix organization, and niche regulation. These findings suggest that LEPC-derived sEV may serve as important signaling mediators within the limbal niche microenvironment, though additional studies are needed to determine their specific functional roles in maintaining niche homeostasis.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Exosomes; Limbal epithelial progenitor cells; Limbal melancoytes; Limbal mesenchymal stromal cells; Limbal stem cell niche; Proteomics; Small extracellular vesicles

Regulatory eosinophils induce the resolution of experimental arthritis and appear in remission state of human rheumatoid arthritis - Andreev, Darja; Liu, Mengdan; Kachler, Katerina; Llerins Perez, Mireia; Kirchner, Philipp; Kölle, Julia; Gießl, Andreas; Rauber, Simon; Song, Rui; Aust, Oliver; Grüneboom, Anika; Kleyer, Arnd; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives: Eosinophils possess pro-inflammatory functions in asthma. However, our recent studies have suggested that innate lymphoid cells type 2 (ILC2s) and eosinophils have proresolving properties in rheumatoid arthritis (RA). Nothing is known yet about the mechanisms determining the double-edged role of eosinophils. Therefore, we investigated whether asthma, a paradigm eosinophilic disease, can elicit resolution of chronic arthritis. Methods: Ovalbumin-triggered eosinophilic asthma was combined with K/BxN serum-induced arthritis, where lung and synovial eosinophil subsets were compared by single-cell RNA sequencing (scRNA-seq). To investigate the involvement of the ILC2-interleukin-5 (IL-5) axis, hydrodynamic injection (HDI) of IL-25 and IL-33 plasmids, IL-5 reporter mice and anti-IL-5 antibody treatment were used. In patients with RA, the presence of distinct eosinophil subsets was examined in peripheral blood and synovial tissue. Disease activity of patients with RA with concomitant asthma was monitored before and after mepolizumab (anti-IL-5 antibody) therapy. Results: The induction of eosinophilic asthma caused resolution of murine arthritis and joint tissue protection. ScRNA-seq revealed a specific subset of regulatory eosinophils (rEos) in the joints, distinct from inflammatory eosinophils in the lungs. Mechanistically, synovial rEos expanded on systemic upregulation of IL-5 released by lung ILC2s. Eosinophil depletion abolished the beneficial effect of asthma on arthritis. rEos were consistently present in the synovium of patients with RA in remission, but not in active stage. Remarkably, in patients with RA with concomitant asthma, mepolizumab treatment induced relapse of arthritis. Conclusion: These findings point to a hitherto undiscovered proresolving signature in an eosinophil subset that stimulates arthritis resolution.
CRIS-Team Scopus Importer:2020-11-20
Keywords: arthritis; autoimmune diseases; cytokines; immune system diseases; inflammation; rheumatoid

Retinal Microcirculation as a Correlate of a Systemic Capillary Impairment After Severe Acute Respiratory Syndrome Coronavirus 2 Infection - Hohberger, Bettina; Ganslmayer, Marion; Lucio, Marianna; Kruse, Friedrich; Hoffmanns, Jakob; Moritz, Michael; Rogge, Lennart; Heltmann, Felix; Szewczykowski, Charlotte; Fürst, Julia; Raftis, Maximilian; Bergua, Antonio; et al. (Frontiers in Medicine, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), affects the pulmonary systems via angiotensin-converting enzyme-2 (ACE-2) receptor, being an entry to systemic infection. As COVID-19 disease features ACE-2 deficiency, a link to microcirculation is proposed. Optical coherence tomography angiography (OCT-A) enables non-invasive analysis of retinal microvasculature. Thus, an impaired systemic microcirculation might be mapped on retinal capillary system. As recent OCT-A studies, analyzing microcirculation in two subdivided layers, yielded contrary results, an increased subdivision of retinal microvasculature might offer an even more fine analysis. The aim of the study was to investigate retinal microcirculation by OCT-A after COVID-19 infection in three subdivided layers (I). In addition, short-term retinal affections were monitored during COVID-19 disease (II). Considering (I), a prospective study (33 patientspost−COVID and 28 controls) was done. Macula and peripapillary vessel density (VD) were scanned with the Spectralis II. Macula VD was measured in three layers: superficial vascular plexus (SVP), intermediate capillary plexus (ICP), and deep capillary plexus (DCP). Analysis was done by the EA-Tool, including an Anatomical Positioning System and an analysis of peripapillary VD by implementing Bruch's membrane opening (BMO) landmarks. Overall, circular (c1, c2, and c3) and sectorial VD (s1-s12) was analyzed. Considering (II), in a retrospective study, 29 patients with severe complications of COVID-19 infection, hospitalized at the intensive care unit, were monitored for retinal findings at bedside during hospitalization. (I) Overall (p = 0.0133) and circular (c1, p = 0.00257; c2, p = 0.0067; and c3, p = 0.0345). VD of the ICP was significantly reduced between patientspost−COVID and controls, respectively. Overall (p = 0.0179) and circular (c1, p = 0.0189) peripapillary VD was significantly reduced between both groups. Subgroup analysis of hospitalized vs. non-hospitalized patientspost−COVID yielded a significantly reduced VD of adjacent layers (DCP and SVP) with increased severity of COVID-19 disease. Clinical severity parameters showed a negative correlation with VD (ICP) and peripapillary VD. (II) Funduscopy yielded retinal hemorrhages and cotton wool spots in 17% of patients during SARS-CoV-2 infection. As VD of the ICP and peripapillary regions was significantly reduced after COVID-19 disease and showed a link to clinical severity markers, we assume that the severity of capillary impairment after COVID-19 infection is mapped on retinal microcirculation, visualized by non-invasive OCT-A.
CRIS-Team Scopus Importer:2021-08-06
Keywords: COVID-19; macula; microcirculation; OCT-angiography; optic nerve head; retina; SARS-CoV-2

Simiate and the focal adhesion kinase FAK1 cooperate in the regulation of dendritogenesis - Rama, Ramya; Derlig, Kristin; Vießmann, Nina; Gossmann, Roman; Oriold, Fabian; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Scientific Reports, 2022)
Despite the crucial importance of dendritogenesis for the correct functioning of neurons, the molecular mechanisms underlying neuronal arborisation are still not well understood. Current models suggest that distinct parts and phases of dendritic development are regulated by the expression of distinct transcription factors, that are able to target the cytoskeleton. Two proteins recently implicated in dendritogenesis are the Focal Adhesion Kinase FAK1 and the Actin-binding protein Simiate. Using heterologous expression systems as well as mouse brain extracts in combination with coprecipitation assays, we show that Simiate is able to associate with FAK1. Differential centrifugation experiments further revealed the interaction to be present in cytosolic as well as nuclear fractions. Inside the nucleus though, Simiate preferentially binds to a FAK1 isoform of 80 kDa, which has previously been shown to regulate transcription factor activity. Investigating the function of both proteins in primary hippocampal cultures, we further found that FAK1 and Simiate have distinct roles in dendritogenesis: While FAK1 increases dendrite length and number, Simiate preferentially enhances growth and branching. However, if being confined to the nucleus, Simiate selectively triggers primary dendrite formation, enhancing transcription activity at the same time. Since the effect on primary dendrites is specifically re-normalized by a co-expression of FAK1 and Simiate in the nucleus, the data implies that the two proteins interact to counterbalance each other in order to control dendrite formation. Looking at the role of the cytosolic interaction of FAK1 and Simiate, we found that neurotrophin induced dendritogenesis causes a striking colocalisation of FAK1 and Simiate in dendritic growth cones, which is not present otherwise, thus suggesting that the cytosolic interaction stimulates growth cone mediated dendritogenesis in response to certain external signals. Taken together, the data show that FAK1 and Simiate exert several and distinct actions during the different phases of dendritogenesis and that these actions are related to their subcellular localisation and their interaction.
CRIS-Team Scopus Importer:2022-07-15

Special characteristics of the transcription and splicing machinery in photoreceptor cells of the mammalian retina - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Cell and Tissue Research, 2015)
Chromatin organization and the management of transcription and splicing are fundamental to the correct functioning of every cell but, in particular, for highly active cells such as photoreceptors, the sensory neurons of the retina. Rod photoreceptor cells of nocturnal animals have recently been shown to have an inverted chromatin architecture compared with rod photoreceptor cells of diurnal animals. The heterochromatin is concentrated in the center of the nucleus, whereas the genetically active euchromatin is positioned close to the nuclear membrane. This unique chromatin architecture suggests that the transcription and splicing machinery is also subject to specific adaptations in these cells. Recently, we described the protein Simiate, which is enriched in nuclear speckles and seems to be involved in transcription and splicing processes. Here, we examine the distribution of Simiate and nuclear speckles in neurons of mouse retinae. In retinal neurons of the inner nuclear and ganglion cell layer, Simiate is concentrated in a clustered pattern in the nuclear interior, whereas in rod and cone photoreceptor cells, Simiate is present at the nuclear periphery. Further staining with markers for the transcription and splicing machinery has confirmed the localization of nuclear speckle components at the periphery. Comparing the distribution of nuclear speckles in retinae of the nocturnal mouse with the diurnal degu, we found no differences in the arrangement of the transcription and splicing machinery in their photoreceptor cells, thus suggesting that the organization of these machineries is not related to the animal's lifestyle but rather represents a general characteristic of photoreceptor organization and function.
EVALuna2:4722

Studying protein function and the role of altered protein expression by antibody interference and three-dimensional reconstructions - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Journal of Visualized Experiments, 2016)
A strict management of protein expression is not only essential to every organism alive, but also an important strategy to investigate protein functions in cellular models. Therefore, recent research invented different tools to target protein expression in mammalian cell lines or even animal models, including RNA and antibody interference. While the first strategy has gathered much attention during the past two decades, peptides mediating a translocation of antibody cargos across cellular membranes and into cells, obtained much less interest. In this publication, we provide a detailed protocol how to utilize a peptide carrier named Chariot in human embryonic kidney cells as well as in primary hippocampal neurons to perform antibody interference experiments and further illustrate the application of three-dimensional reconstructions in analyzing protein function. Our findings suggest that Chariot is, probably due to its nuclear localization signal, particularly well-suited to target proteins residing in the soma and the nucleus. Remarkably, when applying Chariot to primary hippocampal cultures, the reagent turned out to be surprisingly well accepted by dissociated neurons.
EVALuna2:4743
Keywords: Active motif; Antibody interference; Bioengineering; Issue 110; Nuclear proteins; Primary hippocampal cultures; Protein expression; Three-dimensional reconstructions

The BEACH Protein LRBA Promotes the Localization of the Heterotrimeric G-protein Golf to Olfactory Cilia - Kurtenbach, Stefan; Gießl, Andreas; Stromberg, Siv; Kremers, Jan; Atorf, Jenny; Rasche, Sebastian; Neuhaus, Eva M.; Herve, Denis; Brandstätter, Johann Helmut; Asan, Esther; Hatt, Hanns; Kilimann, Manfred W. (Scientific Reports, 2017)
BEACH domain proteins are involved in membrane protein traffic and human diseases, but their molecular mechanisms are not understood. The BEACH protein LRBA has been implicated in immune response and cell proliferation, and human LRBA mutations cause severe immune deficiency. Here, we report a first functional and molecular phenotype outside the immune system of LRBA-knockout mice: compromised olfaction, manifesting in reduced electro-olfactogram response amplitude, impaired food-finding efficiency, and smaller olfactory bulbs. LRBA is prominently expressed in olfactory and vomeronasal chemosensory neurons of wild-type mice. Olfactory impairment in the LRBA-KO is explained by markedly reduced concentrations (20-40% of wild-type levels) of all three subunits ?olf, ?1 and ?13 of the olfactory heterotrimeric G-protein, Golf, in the sensory cilia of olfactory neurons. In contrast, cilia morphology and the concentrations of many other proteins of olfactory cilia are not or only slightly affected. LRBA is also highly expressed in photoreceptor cells, another cell type with a specialized sensory cilium and heterotrimeric G-protein-based signalling; however, visual function appeared unimpaired by the LRBA-KO. To our knowledge, this is the first observation that a BEACH protein is required for the efficient subcellular localization of a lipid-anchored protein, and of a ciliary protein.
EVALuna2:21341